History and Memory of the Marburg Uprising of 1809 and the Napoleonic Wars in Hessen - Vander Ginten, Garrett (My University, 2010)
Our project asked why a monument to the 1809 Marburg Uprising against Napoleon appeared in the city of Marburg when it did (approximately 100 years after the event took place). We asked which social groups created it, what they hoped to achieve by erecting it, and what role the monument played in the landscape of historical commemoration in the city.
Color poster with text and images.
Keywords: Marburg (Germany)--History; Napoleonic Wars, 1800-1815--Monuments--Germany--Marburg; Monuments--Germany--Marburg; Posters